Additively Manufactured Helix Antenna for X-Band Applications - Panusch, David; Hubert, Florian; Bachbauer, Felix; Lomakin, Konstantin; Gold, Gerald (EuCAP 2022 - 16th European Conference on Antennas and Propagation, 2022)
This paper presents an additively manufactured helix antenna for X-Band applications with a center frequency of 10GHz. A comparison between stereolithography and selective laser sintering processes is made. The proposed antenna concept includes a transition from the helix coil to an X-band waveguide, which allows for matching of the antenna to the waveguide. In our measurements, the proposed antennas featured a -10dB-bandwidth of 2.8GHz and a -20dB-bandwidth of 0.28GHz respectively. The suggested manufacturing and design process is, therefore, a major step towards enabling complex antenna geometries.
Keywords: Helix antenna; X-Band; additive manufacturing; SLA; SLS; WR90